Spatial distribution of CD3- and CD8-positive lymphocytes as pretest for POLE wild-type in molecular subgroups of endometrial carcinoma - Jungen, Samuel H.; Noti, Luca; Christe, Lucine; Galvan, Jose A.; Zlobec, Inti; Müller, Michael D.; Imboden, Sara; Siegenthaler, Franziska; Carlson, Joseph W.; Pellinen, Teijo; Heredia-Soto, Victoria; Ruz-Caracuel, Ignacio; et al. (Frontiers in Medicine, 2023)
Introduction Over the years, the molecular classification of endometrial carcinoma has evolved significantly. Both POLEmut and MMRdef cases share tumor biological similarities like high tumor mutational burden and induce strong lymphatic reactions. While therefore use case scenarios for pretesting with tumor-infiltrating lymphocytes to replace molecular analysis did not show promising results, such testing may be warranted in cases where an inverse prediction, such as that of POLEwt, is being considered. For that reason we used a spatial digital pathology method to quantitatively examine CD3+ and CD8+ immune infiltrates in comparison to conventional histopathological parameters, prognostics and as potential pretest before molecular analysis. Methods We applied a four-color multiplex immunofluorescence assay for pan-cytokeratin, CD3, CD8, and DAPI on 252 endometrial carcinomas as testing and compared it to further 213 cases as validation cohort from a similar multiplexing assay. We quantitatively assessed immune infiltrates in microscopic distances within the carcinoma, in a close distance of 50 microns, and in more distant areas. Results Regarding prognostics, high CD3+ and CD8+ densities in intra-tumoral and close subregions pointed toward a favorable outcome. However, TCGA subtyping outperforms prognostication of CD3 and CD8 based parameters. Different CD3+ and CD8+ densities were significantly associated with the TCGA subgroups, but not consistently for histopathological parameter. In the testing cohort, intra-tumoral densities of less than 50 intra-tumoral CD8+ cells/mm2 were the most suitable parameter to assume a POLEwt, irrespective of an MMRdef, NSMP or p53abn background. An application to the validation cohort corroborates these findings with an overall sensitivity of 95.5%. Discussion Molecular confirmation of POLEmut cases remains the gold standard. Even if CD3+ and CD8+ cell densities appeared less prognostic than TCGA, low intra-tumoral CD8+ values predict a POLE wild-type at substantial percentage rates, but not vice versa. This inverse correlation might be useful to increase pretest probabilities in consecutive POLE testing. Molecular subtyping is currently not conducted in one-third of cases deemed low-risk based on conventional clinical and histopathological parameters. However, this percentage could potentially be increased to two-thirds by excluding sequencing of predicted POLE wild-type cases, which could be determined through precise quantification of intra-tumoral CD8+ cells.